Hubungan Antara Konformitas Teman Sebaya dengan Perilaku Merokok Pada Remaja SMK AL-Islam Surakarta - Timur Ninditya Sari, Riska, Aad Satria Permadi, S.Psi, MA (2015)
A teenager at the moment there are many that consume a cigarette .The state of teenagers who had already started smoking often iook in the community around .It is very alarming , the condition of a teenager who behaves smoking can harm the teenager and others who are nearby. Has been clearly written warning in packs of cigarette "smoking kills you".Many cigarette advertisements on the street, and a television that outlines the warning. However, there are still many young people smoking phenomenon in society. One factor may be affected teenagers take up smoking, one of which is conformity peers. The influence of the social environment adolescents is very influential in the process of emergence of smoking behavior in adolescents. This study aims to determine the relationship between peer conformity with smoking behavior in adolescents. Researchers used quantitative methods to achieve the research objectives. Sample in this study were male students SMK Al-Islam Surakarta. The data in this study is the product moment correlation test. The sampling technique used by purposive sampling, namely researchers determine the characteristics of the subject that is the subject of research. The number of subjects in this study were 75 male students of SMK Al-Islam Surakarta. Based on the analysis of the results that the value of the correlation coefficient (r) of 0.090 with significance (p) = 0.221; (p> 0.05), so the hypothesis is rejected, it means that there is no significant positive relationship between peer conformity with smoking behavior in adolescents SMK Al-Islam Surakarta. So it can be said there is no relationship between peer conformity with smoking behavior in adolescents SMK Al-Islam Surakarta. Variable conformity peers in subjects classified as moderate with a mean empirical (RE) 24.93 and the mean hypothetical (RH) 27.5. Variable smoking behavior of the subject is low with average empirical (RE) 38.37 and the mean hypothetical (RH) 50.